2013
DOI: 10.1039/c2cy20373a
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale (111) faceted rock-salt metal oxides in catalysis

Abstract: Facet-specific growth is highly desirable for catalysts, as conversion and selectivity can be altered with increasing amounts of particular active sites. The (100) surface of a rock-salt structure is comprised of alternating oxygen anions and metal cations, similar to the (110) facet. The (111) surface differs substantially in that an ideal (111) surface would consist solely of oxygen anions or metal cations, and cannot exist as-is.However, wet chemical syntheses of MgO(111) and NiO(111) have recently been re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
66
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 172 publications
(323 reference statements)
0
66
0
Order By: Relevance
“…30 According to our recent experimental results, 3 the carbonate species on the (110) planes disappear at a temperature lower than the desorption temperature predicted with atomistic modelling. That phenomenon was assigned to the disappearance of the (110) planes themselves at a temperature temp between 673K and 873 K.…”
Section: Correlation With Catalytic Datamentioning
confidence: 78%
“…30 According to our recent experimental results, 3 the carbonate species on the (110) planes disappear at a temperature lower than the desorption temperature predicted with atomistic modelling. That phenomenon was assigned to the disappearance of the (110) planes themselves at a temperature temp between 673K and 873 K.…”
Section: Correlation With Catalytic Datamentioning
confidence: 78%
“…4 In this respect MgO dissolution and transformation into Mg(OH) 2 brucite represents a prominent system for related investigations since respective insights are also of broader interests for very different fields like the application of refractory materials 9 , passive water treatment 10 , geochemistry and -last but not least -the design of nanomaterials and catalysts. [11][12][13][14][15][16] MgO dissolution processes on well-defined single crystal surfaces have been studied experimentally [17][18][19] and theoretically. [20][21][22] A recent surface science study on the interaction of water with MgO(001) films revealed the emergence of disordered hydroxide surface layers that inhibit the dissolution process at higher pH values.…”
Section: Introductionmentioning
confidence: 99%
“…C hemical evolution and structural transformations at the surface of a material directly influence characteristics relevant to a wide range of prominent applications including heterogeneous catalysis [1][2][3] and energy storage 4,5 . Structural and/or chemical rearrangements at surfaces determine the way a material interacts with its surrounding environment, thus controlling the functionalities of the material [6][7][8][9][10] .…”
mentioning
confidence: 99%